Valuing the Process of Corporate Restructuring - Audra L. Boone; J. Harold Mulherin (Claremont McKenna College, Department of Economics, 2001)
We study the process of corporate restructuring for a sample of 298 firms during the 1989-98 period that announce that they are considering restructuring alternatives. We find that restructuring is a lengthy process, with the majority of the restructuring period occurring prior to any definitive proposals for corporate change. Only 70 percent of the firms that initially propose restructuring later make a definitive proposal to sell either all or part of the firm, with other firms taking themselves out of play or declaring bankruptcy. Hence, the market reaction to the initial restructuring announcement underestimates the full wealth effects of completed restructurings. The estimate of the full value of restructuring across the sample firms averages 7.5 percent, with the greatest gains of 30 percent accruing to firms that are acquired. The average gain for the full restructuring period for firms divesting a unit is 5 percent, which is roughly double that estimated for the initial announcement in prior studies of corporate divestitures.
Keywords: 330